(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Background: A primigravida female patient of age 22 years came to NIA Prasuti ward on date 25th August 2019 with chief complaint of Amenorrhea since 9 months and labor pain since morning with no history of leaking and bleeding per vaginal. Methodology: The patient first visited NIA OPD on 2nd April 2019 for routine Antenatal check up with 5th months of pregnancy. Thereafter she was regularly visiting NIA Prasutitantra OPD for her routine ANC check up and was given routine Ayurvedic anetanatal medications like Mukta Shukti Bhasma and Shatawari churna with milk, Punarnawa Mandoor with buttermilk. She also followed all prenatal advice given to her time to time. The patient had not reported any complication related to pregnancy, or medical problems and side-effects of medications during her course of pregnancy. Patient had given Bala siddha Taila Matra Basti from 37 weeks of gestation twice a week up to the delivery and Bala siddha Taila Yoni Pichu during her active phase of labor up to full dilatation of cervix. Result: A full term normal delivery with right medio-lateral episiotomy with vertex presentation delivered an alive healthy male child of weight 2.7kg on 25th August 2019 at 2:00pm.